Analisis Dampak Akuisisi Pada PT XL Axiata Tbk Terhadap PT Axis Telkom Indonesia - Imam Ari Fadhilah; Muhammad Rizki Mashuda; Tegas Sidiq Tri Pamungkas; Endang Kartini Panggiarti (Jurnal Manajemen Kreatif dan Inovasi, 2024)
Abstrac.This research investigates the impact of acquisitions on company financial performance. By analyzing financial data of a number of companies that have undergone acquisition process, this research aims to assess changes in key financial indicators such as net profit, revenue and cash flow. The research method for this research is a literature review to find information on financial reports and company performance. The impact caused by post-acquisition is that the company's financial performance has increased, especially profitability and activity. However, the aspects of liquidity and solvency did not experience significant changes. There were no negative changes in the company's financial performance. The findings of this research can provide insight into the effectiveness of merger and acquisition strategies in increasing or decreasing a company's financial performance. Managerial implications and recommendations for stakeholders will be discussed in the context of the results of this research.